UJI SENSORIS MI BASAH FORTIFIKASI LONTAR (Borassus flabeliffer L.) UNTUK MENINGKATKAN NILAI TAMBAH BAHAN PANGAN LOKAL NTT - Eny Idayati (Politeknik Pertanian Negeri Kupang, 2016)
Lontar (Borassus flabeliffer L.) fruit is one of the typical fruit East Nusa tenggara (NTT) province, rich in bioactive compounds, containing beta-carotene. The purpose of this study was to test the sensory wet noodles, extra fortification ejection as well as analyzing the feasibility of the production of wet noodles fortified ejection. The study was designedusingcompletely randomized design with two treatments.First treatment was the fortification of palm extract about 30, 40, and 50% (F). And the second treatment was the wheat flour with a protein content about 8, 10, and 12% (T). About 25 trained panelists were testing the sensory properties of treated noodles. The sensory properties included hedonic test for color, smell, texture, firmness and flavor in general and bitter taste on the tongue, followed by calculation of the percentage of each category. Data were analysed using ANOVA and continued with DMRT.The results showed the treatment fortification F1 (30%) and the use of wheat flour T1 (8%),was Â the most preferred by the panelists. The panelists were also asked to rate the bitterness of tne noodles on their tongue and none sampledemonstrated a bitter taste. The business analysis of making wet noodles with treatment F1T1 generated revenue cost ratio about 1.221 which indicates that the business is feasible or profitable.